2020
DOI: 10.1021/acsaem.9b02501
|View full text |Cite
|
Sign up to set email alerts
|

Designed Assembly of Porous Cobalt Oxide/Carbon Nanotentacles on Electrospun Hollow Carbon Nanofibers Network for Supercapacitor

Abstract: Porous and hollow nanomaterials have been an exciting research area for numerous next-generation technological applications. However, it is still a challenge to assemble porous and hollow nanostructures of appropriate composition and characteristics in designed architectures. Here, we report a self-templated metal− organic frameworks based strategy for the synthesis and engineering of porous and hollow nanostructures in designed architectures by developing graphitic-carbonintermingled porous Co 3 O 4 nanotenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 56 publications
0
55
0
4
Order By: Relevance
“…The third method is to use coaxial electrospinning to prepare electrospun fiber precursor with core-shell structure and then the precursor electrospun fibers were calcined at high temperature, which can also result in the hollow structure fiber (131). Dai et al (132) reported a onepot direct electrospinning, using coaxial electrospinning to prepare hollow nanofibers.…”
Section: Hollow Electrospun Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The third method is to use coaxial electrospinning to prepare electrospun fiber precursor with core-shell structure and then the precursor electrospun fibers were calcined at high temperature, which can also result in the hollow structure fiber (131). Dai et al (132) reported a onepot direct electrospinning, using coaxial electrospinning to prepare hollow nanofibers.…”
Section: Hollow Electrospun Fibersmentioning
confidence: 99%
“…Another interesting work for the functional hollow electrospun composite fibers was reported by Mukhiya et al (131). They used coaxial electrospinning and hydrothermal methods to prepare hollow Co 3 O 4 with threedimensional (3D) structure ( Figure 10).…”
Section: Hollow Electrospun Fibersmentioning
confidence: 99%
“…(i) CNFs are very economical compared to graphene and carbon nanotubes and can be easily fabricated on a mass scale. (ii) With proper modifications of the electrospinning technique, precursor composition, or position, followed by a postmodification, carbon nanofibers with extraordinary porosity, a high specific surface area, and diverse functionalities can be fabricated [83][84][85][86][87][88]. (iii) CNFs can be directly used as a free-standing electrode without the use of a conductive additive, binder, or current collector.…”
Section: Electrospun-based Fibers As Negative Electrode Materials For Supercapacitorsmentioning
confidence: 99%
“…The sulfur-doped ZIF-67 derived Co 3 O 4 on NF (S-Co 3 O 4 /NF), prepared via the hydrothermal, annealing and sulfurization methods ( Figure 5 b), delivered superior specific capacity of 178 mAh g −1 (1424 F g −1 ) at 1 A g −1 and good cycling stability (81.5% capacitance retention after 8000 cycles at 3 A g −1 ). Mukhiya et al [ 94 ] synthesized binder-free 3D porous Co 3 O 4 /C@HCNFs (HCNFs = hollow carbon nanofibers) by the preparation of graphitic-carbon-intermingled porous Co 3 O 4 nanotentacles, which exhibit an excellent specific capacity of 1623 F g −1 at 1 A g −1 and long cyclic life, as well as good rate capability ( Figure 5 c). Bao et al [ 95 ] utilized ZIF-67 as the template and NaH 2 PO 2 as the etching agent to construct a series of Co 3 O 4 embedded α-Co/Ni(OH) 2 hollow nanocages ( Figure 5 d).…”
Section: Mofs As Precursors For Scsmentioning
confidence: 99%
“… Schematic illustration for the preparation and electrochemical properties of ( a ) hollow Co 3 O 4 arrays on carbon cloth: Step I, electrochemical deposition; Step II, in situ growth; and Step III, two steps annealing [ 92 ]. ( b ) S-Co 3 O 4 electrode [ 93 ], ( c ) 3D Co 3 O 4 /C@HCNFs nanocomposite [ 94 ] and ( d ) α-CoNi(OH) 2 @Co 3 O 4 -70 nanocage [ 95 ]. ( a , b , d ) Elsevier, 2020.…”
Section: Figurementioning
confidence: 99%